Application of Hybrid Fuzzy Logic Controller for Controlling AFR Engine - Nekooei, Mohammad Javad; Koto, Jaswar (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
The Kyoto Protocol (1997) has been a turning point for future economic and environmental policies for both industrialized and developing countries. The vehicle engine manufacturers are continuously working towards reducing fuel consumption and emissions while maintaining optimum performance by keeping the Air to fuel ratio (AFR) as close to the stoichiometric value of 14.7. In the present paper, new simulation model using Matlab Simulink for a SI (Spark-Ignition) engine has been developed that included all engine dynamic models such as dynamic model of the throttle body, a lambda dynamic model, a model of the intake manifold dynamic, and models of engine torque and fuel injection dynamic. Then, to control the AFR in SI engines, new controllers were proposed to maximize fuel economy and minimize exhaust emissions. A hybrid fuzzy logic controller (HFLC) was created by combining a PID control and fuzzy control. However, this model was validated using the results from engine for various constant load operation tests such as 40 Nm, 50 Nm and 60 Nm but this paper only presented operation at 60 Nm. The simulation results founded that the maximum and minimum AFR for convectional look-up and HFLC methods were (16.80, 12.4) and (15.02, 14.4) respectively. Simulation results from HFLC were lower than other methods such as Sliding Mode Control (SMC), Neural Network (NN), Proportional–Integral controller (PI) and Model-based Predictive Control (MPC) extracted from publishing data.